2014
DOI: 10.1021/tx5000409
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Metabolite Trapping Screens and Potential Pitfalls: Bioactivation of a Homomorpholine and Formation of an Unstable Thiazolidine Adduct

Abstract: Successful early attrition of potential problematic compounds is of great importance in the pharmaceutical industry. The lead compound in a recent project targeting neuropathic pain was susceptible to metabolic bioactivation, which produced reactive metabolites and showed covalent binding to protein. Therefore, as a part of the backup series for this compound several structural modifications were explored to mediate the reactive metabolite and covalent binding risk. A homomorpholine containing series of compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 20 publications
2
25
2
Order By: Relevance
“…Following LC‐UV analysis (Figure a) of samples from incubations conducted in the presence or absence of GSH, a major GSH adduct was identified with a mass increase of 190.0023 Da (Figure b), and the resulting MS 2 analysis was triggered by the isotope‐pattern default setting. Further structural analysis suggested that the GlyCys adduct was rearranged to form a thiazolidine adduct with a proposed structure shown in Figure c, comparable with a rearrangement that was previously reported in previous literatures . Overall, this assay successfully identified unusual GSH adducts and provided structure and semiquantitative information of glutathione adducts.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Following LC‐UV analysis (Figure a) of samples from incubations conducted in the presence or absence of GSH, a major GSH adduct was identified with a mass increase of 190.0023 Da (Figure b), and the resulting MS 2 analysis was triggered by the isotope‐pattern default setting. Further structural analysis suggested that the GlyCys adduct was rearranged to form a thiazolidine adduct with a proposed structure shown in Figure c, comparable with a rearrangement that was previously reported in previous literatures . Overall, this assay successfully identified unusual GSH adducts and provided structure and semiquantitative information of glutathione adducts.…”
Section: Resultssupporting
confidence: 83%
“…Although the above XoPI and DDA-NL will effectively identify most GSH adducts, in a few cases, structural rearranged GSH-adducts could escape identification as reported in the previous literatures 24,25 and would result in false negatives. Therefore, in our method, by employing LC-UV coupled with HRMS, even if both MS settings fail to identify GSH adducts, extra peaks in UV spectra in the presence of glutathione will be observed, and their m/z of GSH adducts appearing as unique isotopic doublet peaks will be obtained.…”
Section: Assay and Analytic Strategymentioning
confidence: 84%
“…The first involved GSH, the routine industry standard for trapping soft electrophilic reactive metabolites. GSH does not routinely adduct with aldehydes, though some literature data suggests this can occur . Saturated aldehydes generally require a nitrogen‐based trapping agent, such as methoxyamine, which forms a stable Schiff base adduct .…”
Section: Resultsmentioning
confidence: 99%
“…GSH does not routinely adduct with aldehydes, though some literature data suggests this can occur. [5] Saturated aldehydes generally require a nitrogen-based trapping agent, such as methoxyamine, which forms a stable Schiff base adduct. [6][7][8] The incubation of CPAQOP with GSH did not produce an adduct (data not shown); instead, only the methanol adducts were detected, confirming that the reactive intermediate was not a soft electrophilic species.…”
Section: Glutathione (Gsh) and Methoxyamine Trapping Experimentsmentioning
confidence: 99%
“…In some instances, in vitro reactive metabolite trapping assays with GSH can lead to false-negatives due to GSH adduct degradation and/or intramolecular rearrangement reactions occurring during incubations leading to modified cyclized adducts not recognized by LC--MS/MS assays since diagnostic fragmentation patterns are no longer useful [65,66]. This has been shown, for example, in studies on the bioactivation of a 1,3-disubstituted piperazine selective melanocortin receptor subtype-4 agonist, MB243 ( Figure 3) [65].…”
Section: Gsh-adduct Structural Rearrangementsmentioning
confidence: 99%